2020
DOI: 10.1002/aenm.202002499
|View full text |Cite
|
Sign up to set email alerts
|

Beyond d Orbits: Steering the Selectivity of Electrochemical CO2 Reduction via Hybridized sp Band of Sulfur‐Incorporated Porous Cd Architectures with Dual Collaborative Sites

Abstract: serious global warming and climate deterioration. As a promising strategy, electrochemical CO 2 reduction reaction (ECRR) not only hinders the increased CO 2 emission, but also favors the generation of high value-added chemical fuels. [1,2] Especially, ECRR can be supplied by renewable energy source such as solar and wind energy, thus exhibiting great potential for practical applications with environmental and economic benefits. [3] However, it is still an enormous challenge to conduct efficient CO 2 electrore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…The redshift of vibrational frequencies for the adsorbed intermediates at larger overpotentials was induced by the changing of the local electric field near the surface, known as the electrochemical Stark effect. [23] Subsequently, DFT calculations were carried out to study the effects of Cu-S coordination and Cu clusters at the molecular level. To provide a plausible explana- In summary, we have demonstrated a Cubased tandem catalyst Cu-S 1 N 3 /Cu x with co-existed atomically dispersed Cu-S 1 N 3 sites and Cu clusters as a powerful CO 2 -to-CO conversion electrocatalyst.…”
Section: Methodsmentioning
confidence: 99%
“…The redshift of vibrational frequencies for the adsorbed intermediates at larger overpotentials was induced by the changing of the local electric field near the surface, known as the electrochemical Stark effect. [23] Subsequently, DFT calculations were carried out to study the effects of Cu-S coordination and Cu clusters at the molecular level. To provide a plausible explana- In summary, we have demonstrated a Cubased tandem catalyst Cu-S 1 N 3 /Cu x with co-existed atomically dispersed Cu-S 1 N 3 sites and Cu clusters as a powerful CO 2 -to-CO conversion electrocatalyst.…”
Section: Methodsmentioning
confidence: 99%
“…The electrocatalytic CO 2 reduction is a prospective strategy for the transformation of CO 2 into fuels and chemicals. In this strategy, CO 2 is used as a raw material to produce valuable products, which can reduce greenhouse gas CO 2 and greatly contribute to solving environmental and energy crises [1][2][3][4][5]. With CO 2 electroreduction, it is usually more difficult to transform multi-carbon products than simple C 1 products [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the above results suggested that the integration of Ag doping and Se vacancies in the CdSe nanorods synergistically enhanced the selectivity to CO. Notably, as shown in Table S2, the Ag-doped CdSe nanorods exhibited a considerable j CO of 19.68 mA cm −2 with FE of 91%, outperforming most related electrocatalysts for CO production [6,17,[40][41][42][43][44][45]. In addition, the durability of the pristine CdSe and 3.1% Ag-CdSe nanorods for CO 2 electroreduction to CO was examined by current-time (I-t) measurements at the potentiostatic of −1.15 V vs. RHE (Fig.…”
Section: Articles Science China Materialsmentioning
confidence: 99%